The revaluation of Ireland - Synnott, Nicholas J. (Statistical and Social Inquiry Society of Ireland, 1900)
In dealing briefly with some of the questions raised before the Royal Commission on Local Taxation, now sitting in London, I feel sure that the opinion of all who have studied the problem at issue will be that, in so far as such questions relate specially to Ireland, the inquiry should have been held in this country, and that there should have been on the Commission a strong leaven of members having practical knowledge of Irish life, laws, and local administration. I make only one general remark upon the constitution of the Commission (consisting of a member of the Government, some English Government officials, a sprinkling of M.P.'s, and Town Clerks)?that Ireland is practically without representation. The one Irishman on the Commission has, I believe, never lived here, and has little practical acquaintance with Irish local affairs. Many of the anomalies of the English system of rating and valuation do not exist here, and this paper will perhaps show that Ireland has peculiar and difficult problems of her own.
Read Tuesday, January 16th, 1900
Keywords: Land valuation; Griffith's valuation; Taxation; 314.15